When bad thinking happens to good people : how philosophy can save us from ourselves - Nadler, Steven M., 1958-; Shapiro, Lawrence (Princeton University Press, 2021)
"Why the tools of philosophy offer a powerful antidote to today's epidemic of irrationalityThere is an epidemic of bad thinking in the world today. An alarming number of people are embracing crazy, even dangerous, ideas. They believe that vaccinations cause autism. They reject the scientific consensus on climate change as a "hoax." And they blame the spread of COVID-19 on the 5G network or a Chinese cabal. Worse, bad thinking drives bad acting-it even inspired a mob to storm the U.S. Capitol. In this book, Steven Nadler and Lawrence Shapiro argue that the best antidote for bad thinking and acting is the wisdom, insights, and practical skills of philosophy. When Bad Thinking Happens to Good People provides an engaging tour through the basic principles of logic, argument, evidence, and probability that can make all of us more reasonable and responsible citizens. When Bad Thinking Happens to Good People shows how we can more readily spot and avoid flawed arguments and unreliable information; determine whether evidence supports or contradicts an idea; distinguish between merely believing something and knowing it; and much more. In doing so, the book reveals how epistemology, which addresses the nature of belief and knowledge, and ethics, the study of moral principles that should govern our behavior, can reduce bad thinking and bad action. Moreover, the book shows why philosophy's millennia-old advice about how to lead a good, rational, and examined life is essential for escaping our current predicament. In a world in which irrationality has exploded to deadly effect, When Bad Thinking Happens to Good People is a timely and essential guide for a return to reason"--